Dogmáticas de transição, evolução dos sistemas e desafios ao ensino do Direito - Costa Gonçalves, Diogo (2016)
Dogmáticas de transição (dogmatics of transition) are those doctrinal formulations that allow the change of an explanatory paradigm to another without legal and scientific breaks and preserving the identity of the institutes. From the study of three institutes we propose to (i) identify the structure of dogmática de transição and (ii) explain its role in the evolution of systems. We also identify the main challenges that the dogmáticas de transição puts to the legal studies.